Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.11591/ijeecs.v16.i2.pp812-817
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum sensing in single channel and multi-channel cognitive radio networks

Abstract: <p>Sensing the existence or absence of primary user is the major chore of cognitive radio networks. Nevertheless, Spectrum sensing is the core process of cognitive radio and with target to find idle channels.Various detection techniques exist, however, energy detection is considered as the most used detector because of its lower computational cost. In this paper, we proposed a study of throughput for a cognitive radio system. We had two scenarios, in the first scenario; a study of throughput against prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Resource sharing has common challenges with heterogeneous networks. Although densification has observable limits for microwave frequencies, it is shown that denser deployments are advantageous for mmWave bands because of their different propagation characteristics for non-line of sight NLoS and line of sight LoS environments [21,22]. Network sharing has evolved from a novel concept a few years back with the arrival of the third generation (3G) networks to a fundamental feature of the emerging 5G systems.…”
Section: Related Workmentioning
confidence: 99%
“…Resource sharing has common challenges with heterogeneous networks. Although densification has observable limits for microwave frequencies, it is shown that denser deployments are advantageous for mmWave bands because of their different propagation characteristics for non-line of sight NLoS and line of sight LoS environments [21,22]. Network sharing has evolved from a novel concept a few years back with the arrival of the third generation (3G) networks to a fundamental feature of the emerging 5G systems.…”
Section: Related Workmentioning
confidence: 99%